Impacts of weather conditions on destination choice of leisure trips - Muhammad Sabir; Jos Van Ommern; Mark J. Koetse; Piet Rietveld (European Regional Science Association (ERSA), 2010)
The aim of this study is to investigate the impacts of weather conditions on the destination choice for the leisure trips within the Netherlands. This empirical analysis will be based on two main data sources. First, the transportation survey which is obtained from Statistics Netherlands for year 2001 to 2005. This survey contains information about the socioeconomic and travel behavior of individuals. It provides information about the origin and destination of the trip, the day and time on which the trip took place, the mode of transportation use for that trip etc. Weather data is provided by Royal Netherlands Metrological Institute (KNMI) for same period. This data is hourly recorded by 32 weather stations more or less evenly located in the Netherlands. The weather conditions contain information about temperature, precipitation , horizontal visibility and wind during every hour of the day. The two datasets will be linked to obtain combined dataset of transport and weather. Multinomial logit model will be use for the choice decision of individual. A nested logit model will also be applied to estimate the mode choice and destination choice decision simultaneously while controlling for weather conditions.
Keywords: 330